Multi-Hazard Assessment of Bridges in Case of Hazard Chain: State of Play and Application to Vehicle-Pier Collision Followed by Fire - Petrini, Francesco; Gkoumas, Konstantinos; Rossi, Claudio; Bontempi, Franco (Frontiers in Built Environment, 2020)
This study focuses on multi-hazard analysis for bridges, following a two-tier approach. First, it identifies relevant open issues and recent literature developments in the field, presenting data in a meaningful manner, with specific focus on the issues related with the analysis of hazard chain scenario treated as low probability-high consequence events. Second, it describes a practically useful and sufficiently generic approach for efficient computational investigation of hazard-chain scenarios in highway bridges. Following that, the applicability of the approach is exemplified in an appealing and commonly encountered in real-life hazard-chain scenario, in which a multilevel modeling strategy is adopted to assess the structural response under hazard chain scenarios of a highway viaduct. Among the considered scenarios is the impact of a heavy vehicle (tank truck) on the bridge pier, and the fire spread following the collision due to the presence of inflammable material. The bridge structure is a typical 189m long multi-span composite highway viaduct. The impact is modelled with a non-linear transient dynamic analysis that accounts the inertial effect of the global structure, while the fire modelling is performed with non-linear quasi static dynamic analysis focusing on local behavior with a sub-structured model. Then different impact and fire scenarios are considered, including different impact velocities of the truck.